Celle circolari e reti di clasti in letti fluviali a sedimenti grossolani. Alcuni risultati sperimentali - CAU, LUCIANO; BIAGINI E. (2008)
Circle cells and clast networks in gravel-bed rivers. Some experimental results. - Extensive field work, begun in 1995, in highly diverse morphoclimatic environments (Northern England, Iceland, Italy, Southern Africa, Southern Australia and Antarctica) has shown the presence, in gravel-bed rivers, of widespread clast cells, covering sometimes 50% or more of river bar areas. In order to reproduce the same processes in controlled conditions, a large number of flume experiments was carried out from 2003 onwards. We have been able to pinpoint two processes: an alluvial process with a trident-shaped flow which bifurcates in correspondence to the keystone, especially at the thalweg, and a random colluvial process whereby cells formed by bank landslides are exhumed by removal of fines at sub-critical flow rates. A dependence of flow patterns from keystone size has been demonstrated. Clast networks exercise a considerable sheltering effect against bed mobilization, as the network elements tend to dampen the energy of the flow. Similar networks are found in many other natural phenomena, suggesting the existence of an underlying order in nature.